Effect Providing Brain Gym On Improving Cognitive Function In Elderly: Meta-Analysis - Setiawan, Cahyo; Yunita Sari, Apriliyan; Arvita Wijayanti, Anggun (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Cognitive decline with aging impacts quality of life, making it crucial to explore effective interventions. Brain Gym, a program involving simple physical exercises, is proposed to enhance cognitive function, but evidence is mixed. This study aims to conduct a meta-analysis to evaluate the overall effectiveness of Brain Gym in improving cognitive function in the elderly and to identify factors that may influence its effectiveness. Methods:  A meta-analysis of RCTs evaluating Brain Gym for elderly cognitive function. Databases searched included PubMed and ScienceDirect. Data were analyzed using RevMan 5.3. Results: The meta-analysis of Brain Gym interventions in elderly individuals revealed high heterogeneity among studies (I² = 95%) and no significant overall effect (P = 0.62), indicating inconsistent results. Conclusion: Brain Gym shows potential for improving cognitive function in the elderly. Future research should explore specific contexts and populations for more targeted interventions.